Implementation Of The Mobile Service Program For Electronic ID Card Issuance For Persons With Disabilities In Lhokseumawe City - Aulia Putri Sania Nasution; Mauludi Mauludi; Lisa Iryani; Aiyub Aiyub; Arinanda Arinanda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The Mobile Service Program (Program Jemput Bola) represents an innovative public service initiative implemented by the Department of Population and Civil Registration of Lhokseumawe City to improve access to civil registration services for persons with disabilities. This study examines the implementation of this program for Electronic Identity Card (KTP-el) issuance and identifies the obstacles encountered. Utilizing a qualitative descriptive approach with case study design, data were collected through observation, in-depth interviews with nine purposively and accidentally selected informants, and documentation. Data validity was ensured through source and technique triangulation. Analysis followed Robert K. Yin's case study framework. The findings reveal that while the program has been implemented, it has not yet achieved optimal performance. Communication aspects remain inadequate, with socialization failing to reach all target groups and limited inter-agency coordination. Resources are constrained by insufficient human resources for field coverage, inadequate facilities (limited recording equipment and operational vehicles), and unstable internet connectivity. Disposition demonstrates strong commitment among implementers despite heavy workloads. Bureaucratic structure shows established procedures but suboptimal, inconsistent inter-agency coordination, with conflicting accounts between department and sub-district officials regarding coordination. Four categories of obstacles were identified: limited data on target beneficiaries, ineffective socialization and coordination, inadequate human resources, and insufficient supporting infrastructure. These constraints result in uneven service coverage, preventing full realization of the program's inclusive service objectives. Strengthening program implementation requires enhanced inter-agency coordination, expanded community outreach through village-level engagement, improved facilities, increased competent personnel, and consistent cross-sectoral collaboration.